2022
DOI: 10.3390/coatings12111618
|View full text |Cite
|
Sign up to set email alerts
|

Bonding Mechanism and Process Characteristics of Special Polymers Applied in Pelletizing Binders

Abstract: Pellet ore not only has excellent metallurgical and mechanical properties, but is also an important metallurgical raw material used to solve the problem of increasing depletion of global high-grade iron ore resources. Bentonite has long been widely used in pellet ore production, which is not only expensive but also causes serious metallurgical pollution. Organic binders can form stronger adhesion and cohesion with mineral particles inside the green pellets than capillary forces, which greatly improves the pell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…Numerous studies have demonstrated that replacing or partially replacing bentonite with organic binders is feasible. However, due to their high cost and thermal instability, they are not widely utilized [8][9][10][11] . The use of low-cost solid waste as binder raw materials is also a research hotspot.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that replacing or partially replacing bentonite with organic binders is feasible. However, due to their high cost and thermal instability, they are not widely utilized [8][9][10][11] . The use of low-cost solid waste as binder raw materials is also a research hotspot.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies and research have already been conducted to test organic binders as alternative binders to bentonite [11][12][13][14][15][16][17][18][19][20][21]. A combination of boron compounds with organic binders such as carboxymethyl cellulose (CMC), starch, dextrin, and some organicbased binders was tested [13,14].…”
Section: Introductionmentioning
confidence: 99%